Історична культура в Україні в умовах російсько-української війни - Сморжевська, Оксана Олександрівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
History as the past to justify the present and future, history as a weapon, history as a component of Ukraine’s victory in the Russian-Ukrainian war - this is far from a complete list of the importance of history in modern geopolitical processes. The end of the 20th and the beginning of the 21st centuries were marked by radically new approaches to understanding the presence of history in the public and virtual space, in the educational system, propaganda, conscientious and conventional warfare. A new historical narrative is being formed in Ukraine, aimed at a Ukrainian-centric understanding and interpretation of national history, taking into account regional and ethnic-cultural diversity; inclusion (reintegration) of the history of Ukraine in the European and global context.